Pelatihan Literasi Dan Pengelolaan Keuangan Bagi Masyarakat Desa Sukahening - Iwan Sugianto; Iwan Saputra; Lati Sari Dewi; Siti Amirah Makarim (CV. SINAR HOWUHOWU, 2026)
This community service activity aims to improve the understanding and skills of the people of Sukahening Village in managing family and business finances in a simple, effective, and sustainable manner. The main problems faced by the community are low financial literacy, the lack of habit in recording income and expenses, and limited understanding of financial planning. The implementation methods included counseling, practical training on simple financial recording, interactive discussions, and mentoring. The participants consisted of village residents, MSME actors, and PKK women’s group members, totaling 35 participants. The results of the activity showed an improvement in participants’ understanding of household and business financial management, as indicated by their ability to create simple budgets, record cash flow, and prepare monthly financial plans. This program is expected to enhance the economic independence of the community and support family welfare in Sukahening Village.